Environmental and Genetic Factors in Autism Spectrum Disorders: Special Emphasis on Data from Arabian Studies - Almandil, Noor B. (Int J Environ Res Public Health, 2019)
One of the most common neurodevelopmental disorders worldwide is autism spectrum disorder (ASD), which is characterized by language delay, impaired communication interactions, and repetitive patterns of behavior caused by environmental and genetic factors. This review aims to provide a comprehensive survey of recently published literature on ASD and especially novel insights into excitatory synaptic transmission. Even though numerous genes have been discovered that play roles in ASD, a good understanding of the pathophysiologic process of ASD is still lacking. The protein–protein interactions between the products of NLGN, SHANK, and NRXN synaptic genes indicate that the dysfunction in synaptic plasticity could be one reason for the development of ASD. Designing more accurate diagnostic tests for the early diagnosis of ASD would improve treatment strategies and could enhance the appropriate monitoring of prognosis. This comprehensive review describes the psychotropic and antiepileptic drugs that are currently available as effective pharmacological treatments and provides in-depth knowledge on the concepts related to clinical, diagnostic, therapeutic, and genetic perspectives of ASD. An increase in the prevalence of ASD in Gulf Cooperation Council countries is also addressed in the review. Further, the review emphasizes the need for international networking and multidimensional studies to design novel and effective treatment strategies.